A thematic review on Baba Nyonya relating to cultural features publications from 2014–2024 - Huang, Wenhong; Abdul Rahman, Ahmad Rizal; Darshan Singh, Sarjit Singh; Raja Ahmad Effendi, Raja Ahmad Azmeer (Human Resource Management Academic Research Society, 2024)
The Baba Nyonya is a unique ethnic group that developed under a complex historical and geographical context. The complexity of its culture is a manifestation and result of this uniqueness. With the development of modern society, this unique culture faces both opportunities and challenges. Although many scholars have discussed the various cultural carriers and characteristics of the Baba Nyonya, there is still a lack of comprehensive literature reviews on the overall cultural characteristics of the Baba Nyonya globally. To bridge this gap, this paper utilizes ATLAS.ti 23 software to conduct a thematic review of 26 articles related to Baba Nyonya culture published between 2014 and 2024. Through thematic analysis, four core themes emerged: Cultural Change and Modern Impact, Physical or Material Culture, Social or Behavioral Culture, and Spiritual or Ideal Culture. While diversity is commonly recognized as one of the main cultural characteristics of the Baba Nyonya, this study further elucidates the dynamic cross-cultural integration features of Baba Nyonya culture through the "Three Cultural Layers" theory from the Physical, Social, and Spiritual dimensions. The review points out that although current research on Baba Nyonya culture is already very in-depth, it mainly focuses on identity, cuisine, architecture, and feminism. Additionally, this study emphasizes the possible cultural changes due to the development over time. This research not only provides insights for scholars interested in Baba Nyonya culture but also offers directions for design research based on the cultural characteristics of this ethnic group.